Dicamba-resistant kochia (Bassia scoparia) in Kansas: characterization and management with fall- or spring-applied PRE herbicides. (9th April 2019) - Kumar, Vipan; Engel, Ryan P.; Currie, Randall; Jha, Prashant; Stahlman, Phillip W.; Thompson, Curtis
Abstract: Dicamba-resistant (DR) kochia is an increasing concern for growers in the US Great Plains, including Kansas. Greenhouse and field experiments (Garden City and Tribune, KS, in the 2014 to 2015 growing season) were conducted to characterize the dicamba resistance levels in two recently evolved DR kochia accessions collected from fallow fields (wheat–sorghum–fallow rotation) near Hays, KS, and to determine the effectiveness of various PRE herbicide tank mixtures applied in fall or spring prior to the fallow year. Dicamba dose–response studies indicated that the KS-110 and KS-113 accessions had 5- to 8-fold resistance to dicamba, respectively, relative to a dicamba-susceptible (DS) accession. In separate field studies, atrazine-based PRE herbicide tank mixtures, dicamba + pendimethalin + sulfentrazone, and metribuzin + sulfentrazone when applied in the spring had excellent kochia control (85% to 95%) for 3 to 4 mo at the Garden City and Tribune sites. In contrast, kochia control with those PRE herbicide tank mixtures when applied in the fall did not exceed 79% at the later evaluation dates. In conclusion, the tested kochia accessions from western Kansas had evolved moderate to high levels of resistance to dicamba. Growers should utilize these effective PRE herbicide tank mixtures (multiple sites of action) in early spring to manage kochia seed bank during the summer fallow phase of this 3-yr crop rotation (wheat–corn/sorghum–fallow) in the Central Great Plains.